Navigating Religious Harmony: A Case Study of the ASEAN Youth Interfaith Camp (AYIC) - R. Budidarmo Pramudji Kuntjoro-Jakti; Abhiram S. Yadav (International Journal of Interreligious and Intercultural Studies, 2022)
This paper serves as a narration of Indonesia’s contribution in concretising the ASEAN Declaration on Culture of Prevention (CoP) for a Peaceful, Inclusive, Resilient, Healthy, and Harmonious Society through the ASEAN Socio-Cultural Community (ASCC) Pillar. To that end, Indonesia assigns the ASEAN Senior Offiials Meeting on Youth (SOMY) as the appropriate lead sectoral body to advance the ASEAN CoP and its practical platform for the ASEAN youths to play a signifiant proactive role in propagating tolerance on religious diversity towards social harmony. With this in mind, it is hoped that the ASEAN Youth Interfaith Camp (AYIC) can give a meaningful contribution in supporting the regional efforts to enhance religious tolerance and the value of moderation at all levels. Furthermore, AYIC may contribute towards alleviating the emergence of new geopolitical, geoeconomics, and geostrategic challenges through its post-event initiatives that have a direct impact towards building community characteristics that is ingrained with tolerance and deference towards religious diversity. In light of the incoming Indonesia’s Chairmanship of ASEAN in 2023, this paper attempts to chart the policy prospect that Indonesia should take in fostering interfaith tolerance and harmony amongst youth across ASEAN so as to support the regional efforts to enhance peaceful co-existence in Southeast Asia.